2017
DOI: 10.1007/s12031-017-0957-2
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide-Releasing Molecule-2 Inhibits Connexin 43-Hemichannel Activity in Spinal Cord Astrocytes to Attenuate Neuropathic Pain

Abstract: Carbon monoxide-releasing molecule (CORM-2) acts as a carbon monoxide (CO) deliverer in a more controlled manner without altering carboxyhemoglobin level and exerts potential function in inhibiting inflammation and/or acute nociception. However, the regulatory mechanism of CORM-2 on spinal nerve ligation (SNL)-induced neuropathic pain is not currently clear. Our study aims to investigate the role of CORM-2 in neuropathic pain and the underlying mechanism. We found that spinal cord astrocytes were dramatically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The expression changes of Cx43 following pain is still inconclusive (Table 2). Multiple studies have shown that Cx43 is upregulated in astrocytes following nerve ligation and spinal cord injury, and that inhibition of Cx43 can attenuate pain hypersensitivity (Wu et al, 2011; Chen et al, 2012, 2014, 2018; Shen et al, 2014; Neumann et al, 2015; Robinson and Dougherty, 2015; Choi et al, 2016; Hang et al, 2016; Kaji et al, 2016; Mao et al, 2017a,b; Wang and Sun, 2017; Yang et al, 2018). On the contrary, few studies showed that a decrease of Cx43 following nerve injury could contribute to pain hypersensitivity (Xu et al, 2014; Morioka et al, 2015; Zhang et al, 2016).…”
Section: Astrocytes and Cx43 In Chronic Painmentioning
confidence: 99%
“…The expression changes of Cx43 following pain is still inconclusive (Table 2). Multiple studies have shown that Cx43 is upregulated in astrocytes following nerve ligation and spinal cord injury, and that inhibition of Cx43 can attenuate pain hypersensitivity (Wu et al, 2011; Chen et al, 2012, 2014, 2018; Shen et al, 2014; Neumann et al, 2015; Robinson and Dougherty, 2015; Choi et al, 2016; Hang et al, 2016; Kaji et al, 2016; Mao et al, 2017a,b; Wang and Sun, 2017; Yang et al, 2018). On the contrary, few studies showed that a decrease of Cx43 following nerve injury could contribute to pain hypersensitivity (Xu et al, 2014; Morioka et al, 2015; Zhang et al, 2016).…”
Section: Astrocytes and Cx43 In Chronic Painmentioning
confidence: 99%
“…Cx43 expression appears to be upregulated within the spinal cord grey matter following a spinal cord injury, oxaliplatin and bortezomib-induced peripheral neuropathy. [37][38][39][40][41][42][43]…”
Section: Connexinsmentioning
confidence: 99%
“…50) The NLRP3 inflamasome complex was activated following a CCI in mice. 37) Although a direct link between increased astrocytic Cx43 and activation of NLRP3 inflammasome was not demonstrated, they speculated that nerve injury evoked increased Cx43 hemichannel activity, resulting in increased ATP release, which in turn, activated NLRP3 inflammasome. 37) Other yet-to-be-identified substances that fit though the hemichannel could also activate other enzymes and lead to nociceptive hypersensitivity.…”
Section: Biographymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Cx43 increased expression has been associated with the maintenance of the late-phase of neuropathic pain in mice (Chen et al, 2012 , 2014 ). Accordingly, the use of Gap26 -a Cx43 hemichannel blocker- attenuated the pain hypersensitivity in a mice cancer pain model (Li et al, 2017 ) and CORM-2—a CO donor and inhibitor of Cx43 hemichannels (León-Paravic et al, 2014 ) also decreased the levels of neuropathic pain in mice (Wang and Sun, 2017 ). Currently, the exact mechanism by which Cx43 hemichannels and/or GJCs present in spinal astrocytes are involved in pain-like behavior remains unknown.…”
Section: Connexin and Pannexin -Mediated Glia-to-neuron Communicationmentioning
confidence: 99%